Reproductive evaluations in female rat offspring exposed to metformin during intrauterine and intrauterine/lactational periods - Forcato, Simone; Montagnini, Bruno Garcia; Marino de Goes, Maria Luiza; Barrionuevo da Silva Novi, Daniella Regina; Inhasz Kiss, Ana Carolina; Ceravolo, Graziela Scalianti; Ceccatto Gerardin, Daniela Cristina (Elsevier B.V., 2019)
Metformin (MET) is a widely-used drug for the treatment of type 2 diabetes mellitus and gestational diabetes. It is known that metformin crosses the placenta and can to be transferred through milk. In vitro studies show that MET decreases gonadotropin-releasing hormone and gonadotropins release in rat neurons, and decreases progesterone and estradiol in rat granulosa cells and androstenedione synthesis in human theca cells. This study evaluated whether MET maternal exposure might interfere with reproductive parameters of female offspring. Wistar female rats were treated with MET 293 mg/kg/day, by gavage, from gestational day (GD) 0 to GD 21 (METG) or GD 0 until lactation day (LD) 21 (METGL). Controls groups received water. An increase in plasmatic estradiol levels was observed during the estrus stage in the METGL group. This result suggests that exposure to MET during gestational and lactational periods might be related to programming in theca and/or granulosa cells during development.
Keywords: Antidiabetic drug; Maternal exposure; Estrous cycle